2012
DOI: 10.1186/2193-1801-1-70
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility pattern of clinical isolates of Pseudomonas aeruginosa isolated from patients of lower respiratory tract infections

Abstract: The present study was conducted to determine the antibiotic susceptibility pattern of Pseudomonas aeruginosa from sputum samples of lower respiratory tract infection patients admitted to different hospitals of Karachi. Most of the hospitals are hampered with high frequency of nosocomial infections generally caused by multiresistant nosocomial pathogen. Among Gram-negative pathogens Pseudomonas aeruginosa considered as most challenging pathogen. The objective of the study was to determine frequency of Pseudomon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 19 publications
4
21
2
1
Order By: Relevance
“…Other studies from Pakistan also observed that Imipenem was the most active drug against P. aeruginosa [18,19]. In our study Gentamicin resistance was 76.5% which is similar to the previous study conducted in Pakistan [13] while another study reported 40% resistance [19].…”
Section: Discussionsupporting
confidence: 92%
“…Other studies from Pakistan also observed that Imipenem was the most active drug against P. aeruginosa [18,19]. In our study Gentamicin resistance was 76.5% which is similar to the previous study conducted in Pakistan [13] while another study reported 40% resistance [19].…”
Section: Discussionsupporting
confidence: 92%
“…this may be due to selective use of aminoglycosides in our setup because of their higher adverse effects. Carbapenems are widely used against gram negative and gram positive microbes; sensitivity to Meropenem was 91.55% in our study which is better than a study done in India by Bajpai et al in 201316 and in Pakistan by Fatima et al in 201217 while other studies by Chander et al in 201312 in Nepal and by Sabir et al in pakistan in 201418 showed sensitivity of Carbapenems to be 100% against Pseudomonas , this shows that resistance is developing gradually, as it is being used now in several hospitals in our locality. Highest resistance was seen to Cefoperazone + Sulbactam (83.10%) in our study as opposed to Abbas et al in 20159 and Nadeem et al In 2009 19.…”
Section: Discussioncontrasting
confidence: 64%
“…Highest resistance was seen to Cefoperazone + Sulbactam (83.10%) in our study as opposed to Abbas et al in 20159 and Nadeem et al In 2009 19. resistance to Piperacillin + Tazobactam was 66.20% which is also significantly higher than previously reported by Micek et al2015,15 Abbas et al20159 and Fatima et al 2012 17. Sensitivity to Ceftazidime and Ciprofloxacin was seen to be 71.01% and 66.20% respectively.…”
Section: Discussionmentioning
confidence: 51%
“…11,12 In other clinical settings, P. aeruginosa has demonstrated increasing levels of resistance to previously effective broad-spectrum antibiotics, including aminoglycosides, cephalosporins, extended-spectrum penicillins, and carbapenems. 13,14 In a previous study from 1987 to 2001 from our institution, more than 90% of cases of P. aeruginosa endophthalmitis were susceptible to initially administered antibiotics. 11 Recently, there have been reports of multidrugresistant P. aeruginosa endophthalmitis.…”
mentioning
confidence: 87%